2020
DOI: 10.1080/26410397.2020.1779631
|View full text |Cite
|
Sign up to set email alerts
|

Budgeting for comprehensive sexual and reproductive health and rights under universal health coverage

Abstract: Achieving universal health coverage (UHC) for sexual and reproductive health (SRH) requires informed budgeting that is aligned with UHC objectives. We draw data from Adding It Up 2019 (AIU-2019) to provide critical new country-level and regional, intervention-specific costs for the provision of SRH services. AIU-2019 is a cost-outcomes analysis, undertaken from the health system perspective, which estimates the costs and impacts of offering SRH care in low-and middle-income countries. We present direct cost es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…This has culminated in discussions on ways to reduce maternal mortality by creating awareness among women about safe and unsafe abortion practices [18][19][20]. Indeed, one of the targets of Sustainable Development Goal 3 is to reduce maternal mortality by promoting equitable access to reproductive health services [21][22][23][24]. However, deliberations on access to and awareness of safe abortion practices have yet to include deaf women.…”
Section: Introductionmentioning
confidence: 99%
“…This has culminated in discussions on ways to reduce maternal mortality by creating awareness among women about safe and unsafe abortion practices [18][19][20]. Indeed, one of the targets of Sustainable Development Goal 3 is to reduce maternal mortality by promoting equitable access to reproductive health services [21][22][23][24]. However, deliberations on access to and awareness of safe abortion practices have yet to include deaf women.…”
Section: Introductionmentioning
confidence: 99%
“…There is a corpus of literature on challenges relating to the accessibility of SRH services, especially in sub-Saharan African contexts [ 13 , 16 , 24 – 27 ]. Most studies have reported that challenges such as lack of policies [ 28 , 29 ], low education levels [ 30 ], poverty [ 12 , 24 , 31 , 32 ], culture [ 33 , 34 ], stigma [ 8 , 16 ] and lack of parental support [ 14 , 35 ] contribute to the inability of girls and women to access SRH services. Other studies have also found that a high prevalence of teenage pregnancy is likely linked to factors such as poverty [ 12 , 25 ], illiteracy [ 30 , 36 – 38 ] and lack of awareness of contraceptive methods [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scaling up provision of modern family planning could reduce the unintended pregnancies that often result in unsafe abortion, and doing so could be a cost-effective strategy. Lince-Deroche et al estimated that in Tanzania in 2019, the annual health system costs of providing modern contraception per woman varied from just $0.62 for intrauterine contraceptive devices (IUDs) to $6.54 for injectable methods [40]. Further, in 2019 Sully et al estimated that meeting the contraceptive needs of all women in low-and middle-income [41].…”
Section: Discussionmentioning
confidence: 99%